Urinary l-type fatty acid-binding protein is a predictor of early renal function after partial nephrectomy. (1st January 2017) - Yanishi, Masaaki; Kinoshita, Hidefumi; Mishima, Takao; Taniguchi, Hisanori; Yoshida, Kenji; Komai, Yoshihiro; Yasuda, Kaneki; Watanabe, Masato; Sugi, Motohiko; Matsuda, Tadashi
Abstract: Purpose: Urinary biomarkers of renal injury urinary may identify loss of renal function following nephron-sparing surgery (NSS). This study was designed to evaluate whether urinaryl -type fatty acid-binding protein (l -FABP) is an early biomarker of loss of renal function after NSS. Specifically, the kinetics of urinaryl -FABP level after NSS and its correlation with factors related to ischemic renal injury were analyzed. Methods: This study prospectively evaluated 18 patients who underwent NSS between July and December 2014, including 12 who underwent laparoscopic and six who underwent robot-assisted partial nephrectomy. Urinaryl -FABP concentrations were measured preoperatively and 1, 2, 3, 6, 12, 24, 48, and 72 h after renal artery declamping. Loss of renal function loss was calculated by comparing the effective renal plasma flow, as determined by 99m Tc-mercaptoacetyltriglycine (MAG3) clearance, on the operated and normal sides. The decrease in estimated glomerular filtration rate from before surgery to six months after surgery was also measured. Results: Urinaryl -FABP concentration peaked within 2 h of declamping, which may quantify nephron damage caused by ischemia. The decrease in MAG3 reduction ratio correlated with both the ischemia time and peak urinaryl -FABP concentration. Peak urinaryl -FABP concentration showed a significant correlation with MAG3 reduction ratio. Conclusions: l -FABP is a suitable urinary biomarker for predicting the extent of ischemic renal injury.